Beyond what the eyes can see: art as a way of connecting actors and promoting social innovation - Figueiró, Paola Schmitt; Bittencourt, Bruno Anicet; Oliveira, Nathan Pedroni de; Flores, Katiuscia Thais (Revista de Administração da UFSM, 2023)
Purpose: This paper aims to understand the relationship between actors’ roles in an entrepreneurial ecosystem from the perspective of Quintuple Helix to promote Social Innovation. Methodology: Participatory action research was carried out during the planning and execution of a project involving University, industry, government, and different actors of society inserted in an entrepreneurial ecosystem. Findings: The data were analyzed following Kemmis and Mctaggart (2007): plan, act and observe, and reflect. Based on the Helix concept, the case is characterized as an entrepreneurial ecosystem with the interaction between a group of actors. The results reinforce the importance of collaboration in the process of social innovation and understanding the role of each actor. Practical implications: The results can help public, private, and non-profit organizations identify their actions, reflect on potential partnerships, and design initiatives capable of generating Social Innovation. Social implications: Training of artists to be creators of prints, facilitating their insertion in the job market; integration between students and civil society association; connection between footwear industry and civil society association by the donation of pairs of sneakers for children. Originality/value: This research can help public, private, and non-profit organizations to identify their actions, reflect on potential partnerships, and design initiatives capable of generating social innovation. We emphasize the importance of engagement, collaboration, and value creation for those involved in social innovation processes.